DIFFERENCES AND RELATIONSHIPS ON SELF-EFFICIENCY AND DISCIPLINE CHARACTER OF HIGH SCHOOL STUDENTS - Fauzi, Ahmad; Aldila, Febri Tia; Hakhumyan, Grant (Program Studi Pendidikan Fisika FKIP Universitas Jambi, 2024)
This research aims to determine the results of student descriptive statistics on the variables of self-efficacy and disciplinary character of high school students in physics subjects. Then, this research also aims to determine the differences and relationships between self-efficacy and the disciplinary character of high school students in physics subjects at the two schools that were the research locations. The method used in this research is a mixed method. The results of the research show that Junior High School 6 Batanghari obtained superior self-efficacy and discipline character scores compared to Junior High School 11 Batanghari. Based on the t-test which states the data comparison is smaller than 0.05 and the correlation test states the data results are smaller than 0.05. This research shows that there are differences and relationships between self-efficacy and the disciplinary character of high school students in physics subjects at the two schools that were the research locations. The novelty in this research is to examine students' self-efficacy and character in learning physics. The results of this research provide implications for physics subject teachers to provide appropriate interventions to develop students' disciplined character with adequate self-efficacy.